Therapeutic potential of bioactive peptides against Lactococcus petauri in Nile tilapia - Vaneci-Silva, Daiane [UNESP]; de Abreu Reis Ferreira, Daniel [UNESP]; Oliveira, André do Vale [UNESP]; Lima de Sousa, Elielma [UNESP]; Gomes, Fernando Cardoso [UNESP]; Assane, Inácio Mateus [UNESP]; Pilarski, Fabiana [UNESP] (Elsevier, 2025)
Lactococcus petauri is an emerging pathogen causing piscine lactococcosis in various aquatic species. This disease has been increasingly reported as a cause of mortality in aquaculture. Due to the indiscriminate use of antimicrobials and to promote viable alternatives for their replacement, bioactive peptides with antimicrobial properties can be explored as tools against bacterial infections. Thus, the objective of this study was to identify the pathogen responsible for a mortality outbreak in cage-cultured Nile tilapia (Oreochromis niloticus), assess its pathogenicity, and evaluate the therapeutic efficacy of a commercial bioactive peptide and florfenicol against L. petauri. The bacterium was isolated from affected Nile tilapia exhibiting external and internal hemorrhages, ocular opacity, anorexia, and ascites. Koch's postulates were fulfilled by inoculating healthy fish with 3.6 × 107 CFU/mL of the bacterium, which induced clinical signs of generalized hemorrhage, ascites, and melanosis. Histopathological analysis revealed severe lesions in the liver, spleen, kidney, intestine, and heart, confirming the pathogen's high virulence in Nile tilapia. To evaluate potential treatments, fish were divided into six groups: G1) inoculated with L. petauri and treated with 15 mg/kg of bioactive peptide via gavage; G2) inoculated and treated with 15 mg/kg of florfenicol via gavage; G3) inoculated and treated with intraperitoneal injection of bioactive peptide (15 mg/kg); G4) inoculated and left untreated; G5) treated with PBS via gavage; and G6) inoculated with PBS. After 30 days, survival rates were G1: 36.85 %, G2: 16.79 %, G3: 26.44 %, and G4: 6.7 %. Significantly higher survival was observed in groups G1, G2, and G3 compared to G4. Moreover, bacterial persistence was only absent in groups G1 and G3. The study demonstrates the effectiveness of the bioactive peptide in treating L. petauri infections and preventing bacterial persistence in Nile tilapia, suggesting it is a viable alternative to traditional antimicrobials.
Keywords: Aquaculture; Bacterial infection; Brazil; Fish health; Florfenicol; Lactococcosis; Therapeutic efficacy